Prognostic Impact of the Metastatic Lymph Node Ratio on Survival in Gastric Cancer - GÜNAL, ÖMER; YEGEN, ŞEVKET CUMHUR; UPRAK, TEVFİK KIVILCIM (SPRINGER INDIA, 2016)
Research on the prognostic value of lymph node ratio (LNR) in gastric cancer (GC) remains limited and controversial results were obtained. In this study, we aimed to evaluate whether LNR was an independent prognostic factor for gastric carcinoma. A retrospective review of a database of gastric cancer patients was performed to determine the effect of the LNR on the overall survival (OS) and the disease-free survival (DFS). Of the total 135 patients with gastric cancer who underwent resection between March 2012 and December 2013, 44 patients with non metastatic gastric cancer were eligible for analysis. Survival curves were estimated using the Kaplan-Meier method. Cox regression analyses, after adjustments for potential confounders, were used to evaluate the relationship between the LNR and survival. According to the cutoff point 0.37 (37 %), the one-year OS rate for LNR <= 37 % was significantly better than that for LNR > 37 % (91.3 % and 61.9 %, respectively, P = 0.02). The one-year DFS for LNR <= 37 % was significantly better than that for LNR > 37 % (91.3 % and 66.7 %, respectively, P = 0.027). In stratified and multivariate analyses adjusted for age, gender, histology and tumor status, a higher LNR was associated with high pN stage and so associated with worse OS and DFS. Thus, the LNR 37% as a cutoff point was found not to be an independent factor for predicting the one-year OS or DFS in patients with non-metastatic GC. The LNR is a prognostic factor in GC. However, no single cut-off value was determined as an independent prognostic factor.
Keywords: Gastric cancer; Lymph node metastasis; Lymph node ratio; Prognosis; NUMBER